PENERAPAN MODEL FLIPPED CLASSROOM BERBANTUAN MEDIA EDUFLIP UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MURID KELAS V PADA MATA PELAJARAN IPAS - Mufidah, Zalfa; Sa'du, Ghina Aulia; Ilahi, Anisa Mutiara; Sundari, Fitri Siti; Trisnayanti, Tia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low cognitive learning outcomes of fifth-grade students in IPAS learning, particularly on the topic of the human respiratory system. The study aimed to improve students’ cognitive learning outcomes through the implementation of the Flipped Classroom model assisted by EduFlip media. This research employed Classroom Action Research (CAR) involving 16 fifth-grade students at a public elementary school in Bogor City. The study was conducted in three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through cognitive achievement tests administered at the end of each cycle and analyzed using descriptive quantitative techniques based on the percentage of classical learning mastery. The findings revealed a gradual improvement in students’ cognitive learning outcomes throughout the implementation of the learning model. The percentage of classical learning mastery was 56.25% in the pre-cycle stage, remained at 56.25% in Cycle I, increased to 68.75% in Cycle II, and reached 93.75% in Cycle III. The results indicate that the implementation of the Flipped Classroom model assisted by EduFlip media contributed to improving students’ cognitive learning outcomes and exceeded the predetermined success criterion of 80% classical mastery. Therefore, the integration of Flipped Classroom and EduFlip media can be considered an alternative instructional strategy to support the improvement of cognitive learning outcomes in elementary school IPAS learning. Keywords: Flipped Classroom, EduFlip, cognitive learning outcomes, IPAS, elementary school students   ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar kognitif murid kelas V dalam pembelajaran IPAS, khususnya pada materi sistem pernapasan manusia. Penelitian ini bertujuan untuk meningkatkan hasil belajar kognitif murid melalui penerapan model Flipped Classroom berbantuan media EduFlip. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang melibatkan 16 murid kelas V di sebuah sekolah dasar negeri di Kota Bogor. Penelitian dilaksanakan dalam tiga siklus, yang masing-masing terdiri atas tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data dikumpulkan melalui tes hasil belajar kognitif yang diberikan pada akhir setiap siklus dan dianalisis menggunakan teknik deskriptif kuantitatif berdasarkan persentase ketuntasan belajar klasikal. Hasil penelitian menunjukkan adanya peningkatan bertahap pada hasil belajar kognitif murid selama penerapan model pembelajaran tersebut. Persentase ketuntasan belajar klasikal sebesar 56,25% pada tahap pra-siklus, tetap sebesar 56,25% pada Siklus I, meningkat menjadi 68,75% pada Siklus II, dan mencapai 93,75% pada Siklus III. Hasil penelitian menunjukkan bahwa penerapan model Flipped Classroom berbantuan media EduFlip berkontribusi terhadap peningkatan hasil belajar kognitif murid serta berhasil melampaui kriteria keberhasilan yang telah ditetapkan, yaitu 80% ketuntasan klasikal. Oleh karena itu, integrasi model Flipped Classroom dan media EduFlip dapat dipertimbangkan sebagai salah satu strategi pembelajaran alternatif untuk mendukung peningkatan hasil belajar kognitif dalam pembelajaran IPAS di sekolah dasar. Kata Kunci: Flipped Classroom, EduFlip, Hasil Belajar Kognitif, IPAS, Murid Sekolah Dasar